The derivation of highest subject questions and the nature of the EPP. Issue 1 (21st February 2020) - Messick, Troy
Abstract : This squib argues that matrix subject wh-phrases reside in SpecCP and moreover during the course of the derivation, never move to SpecTP. This observation raises an immediate problem for languages with a strong EPP requirement on T, such as English. I argue that Chomsky (2013 )'s approach to EPP effects (and other similar approaches) predict the observed pattern, while other prominent theories of the EPP fail to account for it.